UJI EFEK ANTIBAKTERI EKSTRAK ETIL ASETAT DAN KLOROFORM MENIRAN (Phyllanthus niruri Linn) TERHADAP PERTUMBUHAN BAKTERI Staphylococcus aureus ATCC 6538 DAN Escherichia coli ATCC 11229 SECARA in vitro - Rahman, Dwiariawan Tauchid; Sutrisna, EM; Candrasari, Anika (Universitas Muhamadiyah Surakarta, 2012)
Meniran is one of traditional plants that contains several compounds such as terpenoid, flavonoid, and alkaloid that role as antibactrial agent. The aims of the research are to determine the antibacteria effect of extract aethyl acetat and chloroform of meniran. This research was conducted as a laboratory experimental by using post test control group design only. The concentration of extract aethyl acetat and chloroform meniran are 5%, 10%, 20%, 40%, and 80%. The result indicate that extract aethyl acetat of meniran have not effect to Escherichia coli. Meanwhile, to Staphyloccus aureus have an effect (p=0,003). The concentration of the extract chloroform meniran are effective to inhibite the growth of Escherichia coli (p=0,029) and Staphylococcus aureus (p=0,004). The extract aethyl acetat of meniran have an antibacteria effect to Staphylococcus aureus but not to Escherichia coli. Whereas, the extract chloroform of meniran have an antibacteria effect to Staphylococcus aureus and Escherichia coli.Keyword : The aethyl acetat and chloroform extract of Meniran (Phyllanthus niruri L.), antibacteria effect, Staphylococcus aureus and Escherichia coli